2023
DOI: 10.1002/jmv.29186
|View full text |Cite
|
Sign up to set email alerts
|

Increased population susceptibility to seasonal influenza during the COVID‐19 pandemic in China and the United States

Qing Wang,
Mengmeng Jia,
Mingyue Jiang
et al.

Abstract: To the best of our knowledge, no previous study has quantitatively estimated the dynamics and cumulative susceptibility to influenza infections after the widespread lifting of COVID‐19 public health measures.We constructed an imitated stochastic susceptible‐infected‐removed model using particle‐filtered Markov Chain Monte Carlo sampling to estimate the time‐dependent reproduction number of influenza based on influenza surveillance data in southern China, northern China, and the United States during the 2022–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, this period of restricted transmission was followed by increased reported cases of diseases such as HFMD, AHC and pertussis. Other studies have also reported a 74.8–140.1% increase in influenza infections during the 2022–2023 season 39 . This phenomenon, referred to as the “immune gap,” highlights the “broad-spectrum” effectiveness of PHSMs.…”
Section: Discussionmentioning
confidence: 90%
“…However, this period of restricted transmission was followed by increased reported cases of diseases such as HFMD, AHC and pertussis. Other studies have also reported a 74.8–140.1% increase in influenza infections during the 2022–2023 season 39 . This phenomenon, referred to as the “immune gap,” highlights the “broad-spectrum” effectiveness of PHSMs.…”
Section: Discussionmentioning
confidence: 90%
“…Due to the prolonged absence of exposure to the pathogenic microorganism, there is an increasing number of individuals lacking immunity to the influenza virus 49 , 50 . Wang et al 51 quantified the population susceptibility to influenza viruses has increased by 45.1–72.9% after the COVID-19 pandemic. Thus, once pandemic prevention measures are lifted, there is a significant surge.…”
Section: Discussionmentioning
confidence: 99%
“…The weekly positive rate was calculated by dividing the number of positive cases by the total number of cases tested in a given week 10 . The flu epidemic season was deemed to have commenced when the weekly positive rate exceeded 10% and remained at above 10% for the subsequent 2 weeks 18 . The conclusion of the flu epidemic season was determined by the weekly positive rate dropping below 10% and maintaining this level for a minimum of two consecutive weeks 18 .…”
Section: Methodsmentioning
confidence: 99%
“…10 The flu epidemic season was deemed to have commenced when the weekly positive rate exceeded 10% and remained at above 10% for the subsequent 2 weeks. 18 The conclusion of the flu epidemic season was determined by the weekly positive rate dropping below 10% and maintaining this level for a minimum of two consecutive weeks. 18 All analyses in this study were based on natural weeks.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation